The Influence of Differentiated Learning Planning on Learning Achievement in Fiqh Subjects in Merdeka Curriculum at Madrasah Tsanawiyah Negeri 01 Sukoharjo - Siti SIswati; Indah Nurhidayati; Izzun Khoirun Nissa (CV. Creative Tugu Pena, 2025)
This study investigates the influence of differentiated instructional planning on student learning outcomes in the Fiqh subject within the framework of the Merdeka Curriculum at Madrasah Tsanawiyah Negeri 01 Sukoharjo. A quantitative research design was employed, with Grade VII students selected through purposive sampling. Data were gathered using questionnaires and analyzed through linear regression. The results reveal that the level of differentiated instructional planning was moderate but exerted a significant positive effect on student learning outcomes. These findings highlight the importance of tailoring instructional strategies to students’ diverse needs and characteristics, which enhances academic achievement under the Merdeka Curriculum. This study contributes to the growing body of research on curriculum reform in Indonesia by providing empirical evidence that differentiated instructional planning can significantly improve student performance in Islamic education subjects. It offers practical insights for educators and policymakers in optimizing instructional practices that align with the principles of the Merdeka Curriculum, thereby fostering more equitable and effective learning environments.